Case Report: Amphiphysin Antibody-Associated Stiff-Limb Syndrome and Myelopathy: An Unusual Presentation of Breast Cancer in an Elderly Woman - Gogia, Bhanu; Shanina, Elena; Fang, Xiang; He, Jing; Li, Xiangping (Frontiers in Neurology, 2021)
Background: Paraneoplastic stiff limb syndrome (SLS) is rare manifestation of underlying malignancy and could have distinctive features different from the classic stiff person syndrome (SPS). Case description: We present a case of anti-amphiphysin associated paraneoplastic stiff limb syndrome, in an 83-year-old woman with invasive ductal carcinoma of the breast. She presented with rigidity, painful spasm of the distal legs, and asymmetrical fixed posturing of the foot. There is coexisting long tract disturbance and lower extremity weakness. Treatment with diazepam provided symptomatic relief while plasma exchange (PLEX) did not lead to significant clinical improvement. The patient was bedridden within 3 months and passed away within 6 months from symptom onset. Conclusion: This case highlights the importance of recognition of uncommon presentation of stiff person syndrome and their oncological significance. This entity requires a high degree of suspicion for initiation of the proper work up. The rapid identification and treatment of the underlying tumor might offer the best chance for recovery.